(untitled) (CIPEEX, 2022)
NOWADAYS, AMONG ALL THE DIFFICULTIES THAT EDUCATION IN BRAZIL GOES THROUGH, THERE IS A GREAT LACK OF INTEREST ON THE PART OF MANY STUDENTS, FOR ANY SCHOOL ACTIVITY. FOR KUPFER (1995, P. 79), €Œ... THE LEARNING PROCESS DEPENDS ON THE REASON THAT MOTIVATES THE SEARCH FOR KNOWLEDGE€, HIGHLIGHTING THE REASON FOR ITS IMPORTANCE. THEREFORE, THE PRESENT WORK PRESENTS THE PROCESS CARRIED OUT FOR THE CONSTRUCTION OF ONE OF THE MODULES OF THE €ŒUNICASH€ APPLICATION, WHICH AIMS TO ENCOURAGE THE STUDENT TO PERFORM ACTIVITIES THAT WILL BRING BENEFITS. THE APPLICATION WAS DESIGNED LOOKING TO ATTEND THE STUDENTS OF THE EVANGELICAL UNIVERSITY OF ANÁPOLIS, TO TRANSFORM EACH ACTIVITY PERFORMED INTO A SCORE, WHERE THE STUDENT CAN EXCHANGE FOR CONSUMABLE ITEMS. FOR THE CONSTRUCTION OF THE MVP, AGILE METHODOLOGIES WERE USED THAT ARE BASED ON RESEARCH AND REQUIREMENTS GATHERING IN SHORT CYCLES, TO ADD VALUE TO THE PRODUCT. IN PRODUCT DESIGN, LEAN INCEPTION WAS USED FOR BUSINESS ALIGNMENT AND REQUIREMENTS GATHERING, AND IN DEVELOPMENT, SCRUM WAS USED TO FACILITATE PROJECT MANAGEMENT, WITH THE CONSTRUCTION OF THE BACKLOG AND MONITORING OF THE STEPS OF THE DOWNSTREAM FLOW, INVOLVING ALL FRONTS OF WORK SUCH AS DESIGN, API DEVELOPMENT, SCREEN BUILDING AND TESTING. AT THE END OF THESE STAGES OF PROJECT DEVELOPMENT, THE FLOW OF USE OF THE POINTS ACQUIRED BY THE STUDENT WAS OBTAINED, WITH AN INTERFACE IN USABILITY ATTRIBUTES FOLLOWING THE PRINCIPLES OF JAKOB NIELSEN. IT IS WORTH MENTIONING THAT THIS ARTICLE SEEKS TO POINT WAYS TO THOSE INTERESTED IN KNOWING HOW THE PROCESS OF PLANNING AND ELABORATION OF A SOFTWARE APPLICATION HAPPENS. FINALLY, THE PRESENT WORK POINTED OUT WAYS FOR A POSSIBLE SOLUTION TO THE LACK OF MOTIVATION OF STUDENTS, HIGHLIGHTING THE EXCHANGE OF EFFORT IN BENEFITS.